Analytical chemistry : an introduction to pharmaceutical GMP laboratory - Huynh-Ba, Kim (John Wiley & Sons, Inc., 2022)
"Analytical testing in the pharmaceutical industry is necessary to establish drug quality based on science and regulatory compliance. It requires analysts to acquire a solid understanding of analytical chemistry and also a thorough appreciation of pharmaceutical regulatory requirements to address day-to-day challenges and maintain a compliant state. Pharmaceutical laboratories are operated under Good Manufacturing Practices (GMP), thus a knowledge of this regulations is necessary to perform pharmaceutical testing of drug substance and drug products"-- Provided by publisher.
Keywords: Pharmaceutical industry -- Quality control.; Analytical chemistry.; Drugs -- Testing.; Drug development.; Pharmaceutical chemistry.; elektronické knihy; electronic books